2006
DOI: 10.1111/j.1538-7836.2006.01848.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid composition controls thromboplastin sensitivity to individual clotting factors

Abstract: To cite this article: Smith SA, Comp PC, Morrissey JH. Phospholipid composition controls thromboplastin sensitivity to individual clotting factors. 2006; 4: 820-7. Summary. Background: Tissue factor is the active ingredient in thromboplastin reagents used to perform prothrombin time (PT) clotting tests to monitor oral anticoagulant therapy and to screen for clotting factor deficiencies. Thromboplastins are complex mixtures prepared from extracts of brain or placenta, although newer thromboplastins contain r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 37 publications
0
43
0
Order By: Relevance
“…42 Binding of canine clotting factors to human tissue factor has been demonstrated to be decreased compared to the binding of human clotting factors to human tissue factor, the interaction from which thromboplastin sensitivity and the ISI are in part derived. 42,43 To the authors' knowledge, there is no data currently available on thromboplastin sensitivity to canine clotting factors or on an ISI specific for canine samples. It has been demonstrated that correcting PT clotting data by the INR may not produce equivalent results when clotting times are measured using different thromboplastin reagents, 42 so it is unclear to what degree the INR values were affected in the patients in this study considering different laboratories using different thromboplastin reagents were utilized.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…42 Binding of canine clotting factors to human tissue factor has been demonstrated to be decreased compared to the binding of human clotting factors to human tissue factor, the interaction from which thromboplastin sensitivity and the ISI are in part derived. 42,43 To the authors' knowledge, there is no data currently available on thromboplastin sensitivity to canine clotting factors or on an ISI specific for canine samples. It has been demonstrated that correcting PT clotting data by the INR may not produce equivalent results when clotting times are measured using different thromboplastin reagents, 42 so it is unclear to what degree the INR values were affected in the patients in this study considering different laboratories using different thromboplastin reagents were utilized.…”
Section: Discussionmentioning
confidence: 98%
“…The ISI was developed to compensate for differences in thromboplastin potency to human clotting factors. 42 Thromboplastin reagents are comprised of tissue factor from crude extracts of animal or human tissue origin, or recombinant human tissue factor. 42 Binding of canine clotting factors to human tissue factor has been demonstrated to be decreased compared to the binding of human clotting factors to human tissue factor, the interaction from which thromboplastin sensitivity and the ISI are in part derived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…fibrinogen, factors II, VII, IX and X) in blood samples from anticoagulated patients play an important role in explaining discrepancies between the different INR test methods [26]. Additionally, the tissue factor content, the phospholipid composition and differences in ISI calibration may contribute to differences observed in the INR measurements using different thromboplastins [5,9,14].…”
Section: Inr Differences Between Different Pt Assaysmentioning
confidence: 99%
“…Thromboplastin reagents contain either recombinant tissue factor or tissue factor extracted from the brain and placental sources [8]. Thromboplastins also vary in the type and amount of the phospholipid component, which has been shown to influence the results of PT testing [9]. With regard to the phospholipid composition used in the test system, the presence of antiphospholipid antibodies (APL) in a patient's plasma sample may have important implications for the dosing of VKA therapy due to an overestimation of the INR.…”
Section: Introductionmentioning
confidence: 99%